Superfudge - Blume, Judy; Nang Chan Yeema (United States of America Puffin Books, 1980)
Farley Drexel Hatcher, otherwise known as Fundge, plans to be a bird when he grows up. As fas as his older brother, Peter, is concerned, Fudge will grow up to be a big pain!
Keywords: Adult Fiction